2021
DOI: 10.1002/cam4.4143
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic utility of pre‐treatment neutrophil‐to‐lymphocyte‐ratio (NLR) in colorectal cancer: A systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 130 publications
(53 reference statements)
3
35
0
Order By: Relevance
“…In recent decades, studies on the relationship between inflammation and tumor have been more and more extensive, and it has been confirmed that cancer-related inflammation plays a crucial role in tumor growth, invasion and metastasis [4] . Many inflammatory indicators, including NLR, PLR and LMR are prognostic factors for a variety of malignant tumors including breast cancer [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . Lymphocytes play a crucial role in tumor immunity, such as cytotoxic cell death, tumor cell proliferation and migration's inhibition, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, studies on the relationship between inflammation and tumor have been more and more extensive, and it has been confirmed that cancer-related inflammation plays a crucial role in tumor growth, invasion and metastasis [4] . Many inflammatory indicators, including NLR, PLR and LMR are prognostic factors for a variety of malignant tumors including breast cancer [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . Lymphocytes play a crucial role in tumor immunity, such as cytotoxic cell death, tumor cell proliferation and migration's inhibition, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) have been reported as prognostic factors of various cancers [13] , [14] , [15] . Previous studies have found that NLR is not only associated with the prognosis of patients with breast cancer, lung cancer, colorectal cancer, esophageal cancer and cervical cancer [14] , [15] , [16] , [17] , [18] elevated preoperative NLR is also associated with poor prognosis of breast cancer. PLR is considered as a prognostic marker for gastric cancer, ovarian cancer, colorectal cancer, bile duct cancer and other cancers as well[17,19-21].…”
Section: Introductionmentioning
confidence: 94%
“…The neutrophils, lymphocytes, platelets, monocytes and C-reactive protein are all common inflammatory biomarkers and a great number of studies have revealed the prognostic role of NLR, PLR, LMR and GPS in tumors. Several met-analyses demonstrated that elevated pretreatment NLR was a prognostic risk factor in colorectal cancer (HR = 1.57, 95%CI: 1.39-1.78, P < 0.001)[ 36 ], gastric cancer (HR = 1.78, 95%CI: 1.59-1.99, P < 0.001)[ 37 ], laryngeal cancer (HR = 1.76, 95%CI: 1.53-2.03, P < 0.001)[ 38 ] and non-small cell lung cancer patients (HR = 2.86, 95%CI: 2.11-3.87, P < 0.001)[ 39 ]. Furthermore, the prognostic value of GPS has been verified in ovarian cancer (HR = 1.62, 95%CI: 1.38-1.91, P < 0.001), esophageal squamous cell cancer (HR = 1.66, 95%CI: 1.14-2.41, P = 0.008), colorectal cancer (HR = 2.20, 95%CI: 1.88-2.57, P < 0.001) and lung cancer patients (HR = 2.058, 95%CI: 1.51-2.80, P < 0.05) by several meta-analyses[ 14 , 40 - 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kim EY et al veri ed that high preoperative and postoperative NLR were associated with poorer survival rates in patients with gastric cancer [38]. Mate Naszai et al made a systematic review and showed that high NLR was a risk factor for prognosis with the colorectal cancer [39]. Iwai N et al proved that NLR might be an independent prognostic biomarker in patients with unresectable pancreatic cancer [40].…”
Section: Resultsmentioning
confidence: 99%